Primary Pure Squamous Cell Carcinoma of the Gallbladder Locally Invading the Liver, Duodenum, and Stomach: A Case Report and Literature Review - Aldrin C. Alpuerto; Maximo E. Mora; R. Jonathan Robitsek; Sebastian D. Schubl (Case Reports in Surgery)
Primary pure squamous cell carcinoma (SCC) of the gallbladder is an exceptionally rare type of tumor that comprises only 1% of all gallbladder cancer. SCC of the gallbladder portends a worse prognosis than the more common adenocarcinoma variant because of its aggressive invasion to local structures and because it is often diagnosed at an advanced stage. Owing to its rarity, diagnosis and management can be challenging. Herein, we present the case of a 75-year-old female complaining of abdominal pain, nausea, and vomiting. Computed tomography and ultrasonography results of the abdomen were consistent with acute cholecystitis and cholelithiasis. Histologic evaluation of the resected mass revealed a malignant tumor with prominent keratinization, confirming the diagnosis of an invasive primary pure SCC of the gallbladder. Microscopic examination showed direct infiltration to the liver, duodenum, and stomach. This case report describes the hospital course of a patient with SCC of the gallbladder and suggests that gallbladder cancer should be considered as part of the differential diagnosis in elderly patients presenting with acute cholecystitis. In addition, this article will review existing literature to examine the utility of different diagnostic techniques and treatment modalities available in the management of gallbladder cancer.